Badlands. (Economist, 2013)
The article discusses international law related to cyber-warfare and cyberterrorism, with a focus on mutual attacks between North and South Korea as of March 2013. Topics include the challenges of tracing computer hackers; a comparison of state-sponsored cyber-attacks to an act of war; and the publication of a book by international lawyers at the North Atlantic Trade Organization (NATO) on cyber defence, cyber espionage, and cyberspace laws.